2011
DOI: 10.1093/nar/gkr597
|View full text |Cite
|
Sign up to set email alerts
|

A novel TALE nuclease scaffold enables high genome editing activity in combination with low toxicity

Abstract: Sequence-specific nucleases represent valuable tools for precision genome engineering. Traditionally, zinc-finger nucleases (ZFNs) and meganucleases have been used to specifically edit complex genomes. Recently, the DNA binding domains of transcription activator-like effectors (TALEs) from the bacterial pathogen Xanthomonas have been harnessed to direct nuclease domains to desired genomic loci. In this study, we tested a panel of truncation variants based on the TALE protein AvrBs4 to identify TALE nucleases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
612
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(628 citation statements)
references
References 52 publications
12
612
1
3
Order By: Relevance
“…A truncated dTale2 protein (230-610), which is similar to the DNA-bound dHax3 with a premature NTR [16], bound to specified DNA2 with a lower affinity (7.81 µM) ( Figure 1J), indicating that the intact NTR is crucial for the DNA binding ability of dTale2 (148-610), consistent with previous reports that suggest that a fragment encompassing more than 100 residues of the NTR is essential for the full activities of customized TALE fusion proteins [11][12][13][14]. The dTale2 variant protein (148-766) with an extended C-terminal region, bound to specified DNA2 with a comparable affinity (0.70 µM) to dTale2 (148-610) Haishan Figure S10A and S10B), suggesting that dTale2 (148-610) was sufficient to bind to the target DNA.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…A truncated dTale2 protein (230-610), which is similar to the DNA-bound dHax3 with a premature NTR [16], bound to specified DNA2 with a lower affinity (7.81 µM) ( Figure 1J), indicating that the intact NTR is crucial for the DNA binding ability of dTale2 (148-610), consistent with previous reports that suggest that a fragment encompassing more than 100 residues of the NTR is essential for the full activities of customized TALE fusion proteins [11][12][13][14]. The dTale2 variant protein (148-766) with an extended C-terminal region, bound to specified DNA2 with a comparable affinity (0.70 µM) to dTale2 (148-610) Haishan Figure S10A and S10B), suggesting that dTale2 (148-610) was sufficient to bind to the target DNA.…”
supporting
confidence: 88%
“…As shown by the ITC assay, the single mutation (K169A, W232A or R236A) had little effect on the DNA binding ability of dTale2 (148-610), whereas the multiple-mutations of the positively charged amino acids to alanines (K262A/K265A/R266A), (K171A/K262A/ K265A/R266A), (R173A/K262A/K265A/R266A) and (K230A/Q231A/K262A/K265A/R266A) greatly impaired the DNA binding activity of dTale2 (148-610) (Supplementary information, Table S3), implying that these basic amino acids are vital for DNA binding and play synergetic roles in interacting with DNA. Coupled with the previous data from TALEs' applications in vivo [11][12][13][14], it is suggested that the NTR serves as the indispensable "nucleation site" for the TALE-DNA binding both in vitro and in vivo.…”
mentioning
confidence: 70%
“…Importantly, how often does the desired mutation find its way into the target genome? The targeting efficiency of the CRISPR-Cas9 system appears superior to other gene-editing techniques such as zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs), although these techniques set a low bar to reach with efficiencies in human cells ranging from 1 to 50% [7][8][9]. Assuredly, this would be expected to improve with further research, but such inefficiency can produce mosaic cell lines within the embryo, in which some of the cells have been restored to wild type and others remain unrepaired.…”
Section: Scientific Shortcomings: Target Efficiency and Mosaicismmentioning
confidence: 99%
“…Le site de reconnaissance par les TALEN consiste en deux séquences de 14-20 paires de bases (pb) reconnues par chaque monomère de la paire de TALEN, séparées par une séquence de 14-24 pb qui facilite la dimérisation de FokI ( Figure 1D). La taille de la séquence d'espacement entre les sites de liaison de la paire de TALEN dépend, notamment, de la nature de la région carboxy-terminale adjacente aux répétitions [16,18]. C'est au sein de cette séquence d'espacement que la cassure double-brin d'ADN se produit.…”
Section: Talen Et Ingénierie Génomiqueunclassified